1992
DOI: 10.1002/jcu.1870200107
|View full text |Cite
|
Sign up to set email alerts
|

Clinical versus ultrasound examination of the thyroid gland in common clinical practice

Abstract: In a prospective series of 72 patients, clinical and ultrasonographic examination of the thyroid gland were compared in detail. Normal-sized lobes were differentiated from enlarged ones both by inspection and by palpation. When lobar size was assessed by palpation, the estimate was most clearly influenced by increase in width. The correlation between two examiners in lobe size assessment was significant. In the classification of thyroid disease as diffuse, solitary, or multinodular, clinical examination and ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
0
12

Year Published

1995
1995
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(79 citation statements)
references
References 8 publications
6
61
0
12
Order By: Relevance
“…Tan et al (88) reported that 48% of patients with a palpable nodule had more than one nodule detected by US examination and, in these patients, 72% of the nodules had a diameter of %1 cm. Similar results have been reported by others (89,90). Obviously, the increased accuracy in the clinical and laboratory evaluation since the introduction of US-guided fine needle aspiration biopsy (FNAB) of patients with suspected thyroid diseases has led to a dramatic increase in the incidence of thyroid cancer.…”
Section: Clinical Prevalencesupporting
confidence: 81%
“…Tan et al (88) reported that 48% of patients with a palpable nodule had more than one nodule detected by US examination and, in these patients, 72% of the nodules had a diameter of %1 cm. Similar results have been reported by others (89,90). Obviously, the increased accuracy in the clinical and laboratory evaluation since the introduction of US-guided fine needle aspiration biopsy (FNAB) of patients with suspected thyroid diseases has led to a dramatic increase in the incidence of thyroid cancer.…”
Section: Clinical Prevalencesupporting
confidence: 81%
“…Previous studies from areas with different iodine status using ultrasonography as screening in an epidemiological set-up have found nodule prevalences from 4% (1) to 21% (12). The tendency is an increased prevalence of nodules in iodine-deficient populations, but this is not a constant phenomenon (5,14,15,(20)(21)(22). Comparisons of investigations made by different investigators should be done with great care, as classifications are different, the equipment has been improved, and ultrasonography is a subjective procedure.…”
Section: Discussionmentioning
confidence: 99%
“…These last two features might decrease the accuracy of fine needle aspiration biopsy performed with palpation (18,19). Also, there may be other thyroid nodules present that require biopsy based on their size and appearance (14,20,21). Even if the TSH is elevated, FNA is recommended because the rate of malignancy in nodules is similar in thyroid glands involved with Hashimoto's thyroiditis as in normal thyroid glands (22).…”
Section: A B E F Imentioning
confidence: 99%